On the discovery of magnon sidebands in insulating antiferromagnets - White, Robert M.; Yen, William M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
In this article, we reconstruct the course of events which led to the discovery and identificationof magnon sidebands in the optical spectrum of simple antiferromagnetic insulators.